Audit committee and external auditors in government-linked companies: do they play their roles to mitigate earning management? / Memiyanty Abdul Rahim, Anis Syafiqah Khir Shuhaimi and Azizan Zainuddin - Abdul Rahim, Memiyanty; Khir Shuhaimi, Anis Syafiqah; Zainuddin, Azizan (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
The accounting scandals of 1Malaysia Development Berhad in Government- Linked Companies (GLCs) in Malaysia had brought in negative consequences not just to the company but also to the stakeholders of the company. Hence, this study was conducted to examine the possibility of corporate governance monitoring mechanisms from Audit Committee and External Auditors Perspective in mitigating earnings management in GLCs in Malaysia. The data on corporate governance monitoring mechanisms were taken from annual reports of 38 GLCs listed in Bursa Malaysia for three years. This study used discretionary accruals as the proxy of the earnings management, quantified by Modified Jones in 1995. The data analysis was done via SPSS software by using multiple regression. The results showed that four out of five corporate governance monitoring mechanism variables have an insignificant influence on earnings management of GLCs listed in Bursa Malaysia. The external audit fee was the only variable of the corporate governance monitoring mechanism that had an influence on earnings management. This study provides policymakers, board directors, and managers with a set of recommendations that are relevant to the context by enabling a better understanding the impact of audit committee and external auditors on earnings quality.